(untitled) (aSSIST Business Review, 2026)
This study examines the close relationship between organizational culture and employee engagement using the case of S Corporation, a rapidly growing secondary battery manufacturer. It proposes actionable strategies for enhancing employee engagement by fostering a positive organizational culture. Since its acquisition by Israel’s SolarEdge Technologies in 2018, S Corporation has achieved rapid growth, but this expansion has led to cultural differences and conflicts between existing employees and new hires, making it challenging to establish a consistent organizational culture. Survey data from all employees using a Likert scale and open-ended responses were analyzed based on seven key elements of organizational culture (shared values, strategy, structure, management systems, members, technology, leadership style) and three main factors of employee engagement (vigor, dedication, absorption). Results indicate that S Corporation’s employee engagement was generally low, with insufficient shared values, an opaque management system, and inadequate leadership styles negatively affecting engagement. Based on these findings, this study proposes strategies including establishing a clear vision, improving leadership practices, creating fair management systems, promoting work-life balance, and managing external influences to enhance employee engagement in fast-growing companies.